A Systematic Review Examining the Association of Falls With Diabetes‐Related Foot Ulcers - Mike Wu; Mallika Sinha; Chanika Alahakoon; Kristen S. Barratt; Shivshankar Thanigaimani; Jonathan Golledge (Journal of Foot and Ankle Research, 2025)
ABSTRACT Background The aim of this study was to systematically review the risk of falls in people with diabetes‐related foot ulcers (DFU). Methods A systematic search of Medline, Pubmed, Embase, Cochrane and CINAHL was undertaken to identify observational studies reporting falls and containing a group of people with a DFU and a control group with diabetes but no DFU. Risk of bias was assessed by a modified Newcastle–Ottawa Scale. Meta‐analysis was performed using a random effects model. Results Four studies involving 3643 participants with a DFU and 42,436 participants with diabetes but no DFU were included. A meta‐analysis showed high heterogeneity between studies (I2 = 95%) and an increased risk of falls in people with DFU (risk ratio 2.25 and 95% CI 1.05–4.84). One study had a low risk of bias and three studies had a high risk of bias. Leave‐one‐out analyses showed that exclusion of the study with the largest effect on heterogeneity resulted in a risk ratio of 1.80 (95% CI 1.33–2.43 and I2 = 0%). Conclusions Currently available evidence suggests people with a DFU have a higher risk of falls but most past studies have a high risk of bias. Further well‐designed cohort studies are required.